INNOVATION OF EDUCATIONAL MARKETING MIX IN IMPROVING COMPETITIVENESS AT AR RAHMAT JUNIOR HIGH SCHOOL BOJONEGORO - Sahri; Masrokan Mutohar , Prim; Eko Sujianto, Agus (re-JIEM (Research Journal of Islamic Education Management), 2023)
This study aims to examine the innovation of the marketing mix of educational services in increasing competitiveness and customer value at Junior High School Rahmat. This research uses a qualitative approach with a case study method. Data collection was conducted through in-depth interviews, observation, and documentation. The results showed that Junior High School Ar Rahmat has innovated the marketing mix in several aspects, such as product innovation, price, promotion, and place. The innovation is directed to provide added value for customers and increase student’s and parent’s satisfaction. This research provides advice for Junior High School Ar Rahmat in innovating the marketing mix, such as improving service quality, expanding the reach of promotions, offering more varied educational programs, providing financial assistance, and collaborating with educational institutions or companies. This research can provide input for decision-makers in the world of education to innovate the marketing mix in an effort to increase competitiveness and customer value in schools.